2011
DOI: 10.3109/15622975.2011.599213
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced emotional interference on working memory performance in adults with ADHD

Abstract: Our results suggest that difficulties in suppressing attention towards emotionally laden stimuli might result from deficient executive control in ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…The absence of a group difference in emotional-specific interference is in line with some studies (Passarotti et al, 2010a(Passarotti et al, , 2010b but does not correspond to others where emotional interference has been shown when individuals with ADHD were performing EF tasks (Köchel et al, 2014;López-Martín et al, 2013;Marx et al, 2011;Posner et al, 2011).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The absence of a group difference in emotional-specific interference is in line with some studies (Passarotti et al, 2010a(Passarotti et al, , 2010b but does not correspond to others where emotional interference has been shown when individuals with ADHD were performing EF tasks (Köchel et al, 2014;López-Martín et al, 2013;Marx et al, 2011;Posner et al, 2011).…”
Section: Discussionsupporting
confidence: 66%
“…The, to our knowledge, only study on adults reported that subjects with ADHD exhibited lower rates of accuracy in a n-back task compared to control subjects, indicating enhanced EMOTIONAL INTERFERENCE IN CHILDREN WITH ADHD 5 distractibility by emotionally salient stimuli (Marx et al, 2011). Finally, the study of Passarotti et al (2010a) found ADHD-related reduced activity in the ventrolateral prefrontal cortex despite the lack of differences in behavioral performance, which may indicate the use of compensatory strategies.…”
Section: Introductionmentioning
confidence: 93%
“…Lack of perseverance is conceptualized as "the ability to remain focused on a task that may be boring or difficult'' (Whiteside and Lynam, 2001), a behavior being potentially associated with poor executive performances, and with difficulties in overcoming proactive interference in working memory promoting intrusive thoughts and mind wandering (Gay et al, 2008. Recent works have documented that adults with ADHD had low resistance to distraction during working memory task implying sustained attention (Marx et al, 2011;Pelletier et al, 2013). An impairment in working memory is the hallmark of the ADHD neuropsychological profile.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the extensive variability in the populations studied (typically vs. atypically developing, and different age groups), making it difficult to draw parallels between findings and particularly challenging to make predictions for typically developing children. Some authors find only significant slowing in response to negative emotional cues relative to positive or neutral ones ( healthy adult sample : Kensinger and Corkin, 2003; anxious sample of 8- to 30-year-olds : Ladouceur et al, 2009), whereas others report no reaction time (RT) differences by emotion type and instead report impaired accuracy on trials with negative compared to neutral distractors ( adult controls and ADHD participants : Marx et al, 2011). Others have reported varying speed-accuracy trade-offs by emotion type, including higher accuracy but slower RTs for negative compared to neutral stimuli in a non-verbal working memory task with a sample of schizophrenic participants (Becerril and Barch, 2011).…”
Section: Introductionmentioning
confidence: 99%